Antioxidant and Antibacterial Activities of the Essential Oil of Moroccan Tetraclinis articulata (Vahl) Masters - Halima Rabib; Chaimaa Elagdi; Mohammed Hsaine; Hassan Fougrach; Tayeb Koussa; Wadi Badri (Biochemistry Research International)
The purpose of this study is to evaluate and compare the antioxidant and antibacterial activities of essential oil isolated from Tetraclinis articulata (Vahl) leaves, Masters originating in Morocco (Benslimane Region, Atlantic-influenced plain). The analysis of the major compounds of essential oil was performed by gas chromatography and mass spectrometry, and this oil is dominated by bornyl acetate (35.05%), camphor (11.17%), and α-pinene (10.84%). The antioxidant properties were evaluated by the test of the radical trap 2,2-diphényl-1-picrylhydrazyl (DPPH), and the antimicrobial activity of T. articulata essential oil was tested against clinical isolates of Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli which have been inhibited from the 25 μg/mL.